EdTech for Learning in Emergencies and Displaced Settings: A rigorous review and narrative synthesis - Save the Children (Resource Centre, 2018)
Globally, according to UNESCO (2017), 264 million children of primary and secondary school age are out school. UNESCO also estimates that worldwide roughly 100 million young people are fully illiterate. While data on attendance, enrolment, and literacy can be difficult to gather in fragile and conflict-affected settings, estimates suggest that children in these settings are roughly three times more likely to be out of school than children living in stable, but low-income countries.